Afrontamiento al estrés y bienestar psicológico en estudiantes universitarios de Lima y Huancayo - Matalinares C., María Luisa (2017)
The present study aimed to establish the relationship between ways of coping with stress and psychological well-being. A sample of 934 university students from Lima and Huancayo, 16 to 22 years old, was used. Two were the instruments applied: the COPE Inventory (Carver, Scheir y Weintraub, 1989), about coping with stress strategies, adapted to peruvian context. And the Scales of Psychological Well-Being (SPWB), by Carol Ryff (1989), adapted to Peruvian context by Leal and Silva (2010). The results showed that there is a direct and significant relationship between problem-focused and emotion- focused coping with stress strategies and psychological well-being, while other coping strategies obtained a significant but indirect relationship.